Penguatan Layanan Bimbingan dan Konseling Berbasis 7 Jurus BK Hebat Membangun Ketahanan Psikososial, Regulasi Diri, dan Koneksi Belajar Peserta Didik: Strengthening Guidance And Counseling Services Based On 7 Great Guidance And Counseling Strategies To Build Psychosocial Resilience, Self-Regulation, And Learning Connections In Students - Rahman, Taufiq; Aswar, Aswar (Litera Academica Publishing, 2025)
Guidance and Counseling (GC) services play a critical role in addressing the psychosocial challenges faced by students in modern educational settings, particularly those related to academic pressure, emotional regulation, and self-management difficulties. This literature review examines a comprehensive model for strengthening GC services through the implementation of the 7 Jurus BK Hebat Recognize Potential, Regulate Emotions, Foster Resilience, Maintain Consistency, Build Connection, Strengthen Collaboration, and Structure Situations as a holistic framework to enhance students’ psychosocial resilience and learning engagement. The study employs a literature-based methodological approach by analyzing national and international journal articles published within the last 5–10 years, supported by academic books and formal GC regulations. Findings reveal that the seven principles significantly contribute to improving students’ self-regulation, emotional stability, motivation, and social connectedness. The discussion further confirms that integrating these seven principles aligns with the demands of 21st-century school counseling, particularly in its emphasis on preventive approaches, potential development, and strengthened collaboration between teachers, counselors, and parents. Overall, this model demonstrates strong relevance and adaptability for modern school environments, offering long-term implications for students’ academic, social, and emotional development.